ANALISIS PENGEMBANGAN KOMPETENSI PROFESIONAL GURU DALAM PENERAPAN KURIKULUM MERDEKA DI SMPN 1 TANJUNG TEBAT - Rizen Erlangga Rizen Rizen; Julius Julius (STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
This study aims to determine the development of professional competencies in the implementation of the independent curriculum at SMP Negeri 1 Tanjung Tebat and to find out the supporting and inhibiting factors. The background of this research is that teachers do not fully understand the independent curriculum and there is a need for professional competency development to understand the independent curriculum. The method used is qualitative descriptive research with data collection techniques through observation, interviews and documentation. The population in this study is all teachers at SMP Negeri 1 Tanjung Tebat which is 26 people. The sample was selected using a sample extraction technique, namely purposive sampling, namely Islamic Religious Education Teachers who teach in grade 7 and are involved in the implementation of the independent curriculum. The results of the study show that the development of teachers' professional competencies at SMP Negeri 1 Tanjung Tebat is carried out through various efforts such as participating in training, training, workshops, seminars, and involvement in the learning community (KOMBEL). The supporting factors found were the support of the school and facilities. Obstacles found include economy, time constraints and high workload